Microbial fuel cell as innovative approach for bio-electricity generation: A review - Pratibha Singh; Ashima Srivastava; Nupoor Srivastava; Niharika Sinha; Vivek Sharma; Asha Upadhyay (Zaštita Materijala)
The current global scenario is marked by substantial energy demands coupled with limited resources, leading to a widespread energy crisis. Non-renewable energy sources are depleting rapidly, while renewable sources remain underutilized. There is an urgent need for alternative methods of energy generation. In recent times, considerable attention has been directed towards microbial fuel cells (MFCs) due to their favorable operating conditions and the availability of a variety of eco-friendly substrates as fuel. Through the active breakdown of substrates by microorganisms, bioelectricity is produced, offering a sustainable solution to the escalating energy challenges. Extensive research has yielded new insights into Microbial Fuel Cells (MFCs), revealing that a diverse range of carbon sources, including various types of waste, can be effectively utilized with a wide array of microbes. Consequently, the microbial conversion of waste through innovative bioremediation techniques like utilizing MFCs present a potentially attractive alternative to conventional treatment processes in wastewater treatment, facilitating the direct generation of electric energy. This not only aligns with prevailing technological trends but also contributes to cost reduction in the overall process. This article comprehensively examines various components of Microbial Fuel Cells (MFCs), including the anode, cathode, and membrane. To address practical challenges within this field, pragmatic solutions are proposed. The review critically assesses diverse categories of wastes suitable for Bioenergy generation, exploring the associated microorganisms, power output, key advantages, challenges, and limitations and advancements of MFC technology.